Specific Features of Educational and Pedagogical Discourse in the Context of Anthropological Challenges: Socio-Cultural Approach - Kochetkov, Maksim V.; Kovalevich, Igor’ A. (Journal of Siberian Federal University. Humanities & Social Sciences, 2020)
The relevance of the research is due to the destructive influence of digitalization of society, globalization processes, technological and social progress on a person in his spiritual and physical integrity. These are, first of all, such technological and sociocultural factors as virtualization of the individual’s consciousness, cyborgization, loss of subjectivity in the process of merging with information machine complexes, genetic engineering, cloning, pharmaceutical modifying human influence. It is proved that a broad interpretation of educational and pedagogical discourse is adequate for the modern socio-cultural space, which is becoming more complicated for description, which makes it synonymous with such a basic category for pedagogical science as the pedagogical process. The marked tendency is estimated as negative, as the categorical value of basic concepts for pedagogy is lost, the subject of pedagogical science in the system of human Sciences is blurred. Therefore, a highly specialized definition of specific features of pedagogical discourse is justified. It is concluded that the pedagogical category “zone of immediate development” in its socio-cultural hypostasis contributes to the designation of specific features of educational and pedagogical discourse, focusing on specific pedagogical tasks. For example orientation to the zone of the nearest development of the individual in the process of his constant development and self-development assumes permanent diagnostic correction on the part of the teacher in relation to the student. This favors the consistency of the socio-cultural experience transmitted by the teacher with the life experience of the student, the emotional “inclusion” of the latter in the educational process